Implementing the extended TeX layout using PostScript fonts - Rahtz, S (TeX Users Group, 1993)
When Donald Knuth made virtual fonts part of the general TeX repertoire at the end of 1989 [5], at the same time as extending both TeX and METAFONT to support 8-bit input, it immediately became obvious that the world needed a new standard for the layout of fonts. This is not the place to review the discussion of what characters should be in a generalized 256 character text font (see [4, 3]), nor to pass judgement on the proposed solution, finalized at the TeX Users Group meeting in Cork in September 1990, but rather to demonstrate how the layout can be implemented using PostScript fonts (Donald Knuth and Tom Rokicki have already shown how to create PostScript fonts in the original TeX layout, using virtual fonts, implemented in the latter's distributed afm2tfm program) . To remind ourselves what we are aiming at, Fig. 1 shows the new layout using the Extended Computer Modern Roman font (dcr10, from the dc family created by Norbert Schwarz). Some characters needed extra work with METAFONT, but most were created from existing building blocks, and we shall follow this approach with the PostScript fonts.